2020
DOI: 10.1371/journal.pone.0229324
|View full text |Cite
|
Sign up to set email alerts
|

One step beyond a broad molecular phylogenetic analysis: Species delimitation of Adenomera marmorata Steindachner, 1867 (Anura: Leptodactylidae)

Abstract: Taxonomists always have had intense discussions about how species should be delimited and recently many studies have used integrative approaches by combining molecular, morphological, and bioacoustic data. Although these studies are paramount for understanding species diversity, few of them actually formalize species delimitations to the final step of nomenclatural acts. Historically, the Neotropical frog genus Adenomera has been considered as a difficult taxonomic group because it comprises many morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 68 publications
(95 reference statements)
0
13
0
Order By: Relevance
“…Adenomera marmorata shows a variation in chromosome pair 12, which is metacentric in the populations of the state of São Paulo. Thus, Campos et al (2009) hypothesized that it is an interpopulation variation, which was later confirmed by Cassini et al (2020) in a taxonomic study on the group that integrated DNA sequences, morphology, and bioacoustics. The specimen identified by Campos et al (2009) as A. aff bokermanni was collected in the municipality of Santa Branca in the state of São Paulo, which is outside the current distribution of A. bokermanni, which is restricted to the southern region of the state of Paraná (Cassini et al 2020).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Adenomera marmorata shows a variation in chromosome pair 12, which is metacentric in the populations of the state of São Paulo. Thus, Campos et al (2009) hypothesized that it is an interpopulation variation, which was later confirmed by Cassini et al (2020) in a taxonomic study on the group that integrated DNA sequences, morphology, and bioacoustics. The specimen identified by Campos et al (2009) as A. aff bokermanni was collected in the municipality of Santa Branca in the state of São Paulo, which is outside the current distribution of A. bokermanni, which is restricted to the southern region of the state of Paraná (Cassini et al 2020).…”
Section: Discussionmentioning
confidence: 92%
“…The number of cytogenetic studies on anurans has grown in recent years (e.g., Ferro et al 2016 ; Gazoni et al 2018 ; Marciano-Jr et al 2021 ); however, information for some families and/or genera is still scarce. The genus Adenomera comprises common and abundant species, some of which often occur syntopically ( Cassini et al 2020 ), but cytogenetic data for the entire genus are still scant compared to other anuran genera. So far, only six of the 29 described species have been karyotyped.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, we carefully decided to register this species only at the genus level. Second, both genus Adenomera and Ischnocnema present a complex taxonomy (Gehara et al 2013, Cassini et al 2020 (Cruz & Peixoto, 1987) FA, CF 6, 14 Bokermannohyla circumdata (Cope, 1871) FA 13 Bokermannohyla ibitipoca (Caramaschi & Feio, 1990 molecular integrative approaches could elucidate the species complex hypothesis in both groups and arise with new candidate species or an accurate identification. For that reason, we prefer to assign both species only at the genus level.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the only call description available is from the holotype in the original description, from which tissue samples were not collected (and neither were they collected from paratypes). It is important to highlight that species identification within Adenomera should be treated with caution in such cases which acoustic and/or molecular data are not available in a frog genus having a notably high number of undescribed and/or cryptic species (Carvalho & Giaretta 2013a;Fouquet et al 2014;Carvalho et al 2019b;Cassini et al 2020).…”
Section: Introductionmentioning
confidence: 99%